Text on back: 'Maestro San José Cuidad Real'. Mark on back: 'UGT, Brigada de informacion grafic, sindicato de fotografos'
Text on back: 'Maestro San José Cuidad Real'. Mark on back: 'UGT, Brigada de informacion grafic, sindicato de fotografos'.